Preliminary study on sergestid shrimps (acetes) of Sarawak coastal waters based on morphology and pcr-rapd approaches - Christine, Anthonius (Universiti Malaysia Sarawak, UNIMAS, 2012)
Acetes spp. is a type of Sergestid shrimp which is common in Malaysian coastal waters. It is highly gregarious and is a seasonal occurring shrimp. Acetes are locally known as „udang geragau‟ in Peninsular Malaysia. In Sarawak, the locals usually called them as „bubok‟. In Malaysia, this shrimp is made into various food products. This species is also known for its prominent role in ocean food web. Lack of studies on Acetes shrimp inhabiting Sarawak waters had limit the public to maximize the potential role of Acetes shrimp. Therefore, this study aims to record the morphological details of Acetes that occurs in Sarawak coastal waters and carry out preliminary molecular studies on Acetes spp. Based on the morphological characters, the Acetes samples from Bako and Bintulu were identified as Acetes intermedius and Acetes indicus, respectively. The Acetes samples from Kuching failed to be determined up to species level due to its dried state. PCR-RAPD profile from Bako and Bintulu samples had been documented. The percentage of polymorphic bands for sample B is 71.43 %. On the other hand, sample C (Bintulu) showed only two bands unique to the respective species. The percentage of polymorphic bands of Bintulu sample was 50 %. There were two monomorphic bands observed which were 500 bp and 800 bp, respectively.